(3EfHGA GrdZeQ HCHfGA GrdoYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3CeG HYO gPG JYdjb LeYJ ajg MhGOK GdReGf GdPi COQcJg efP ehdOi SfI KdGK hSHYjf hSHYeGFI , hgde LQG s
(3BNQgG (B:s
(3aj hajGJ SfI (B814(3g` , aj CKfGA JQLeI YHOGdQMef Hf eMeO Hf CHj GdhaG s
(3GdLRA GdChds
(3hHYV GdKGfj ef fSNI SGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B69 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B74 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B52 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs